Clinical and Electrophysiologic Characteristics of a Large Kindred with X-Linked Retinitis Pigmentosa Associated with the RPGR Locus. (9th December 2015) - Tzu, Jonathan H.; Arguello, Tania; Berrocal, Audina M.; Berrocal, Maria; Weisman, Alejandra D.; Liu, Mu; Hess, Ditte; Caputo, Michelle; Goldberg, Jeffrey L.; Feuer, William J.; Stone, Edwin M.; Lam, Byron L.
Abstract: Purpose : To phenotypically and genotypically characterize a large Puerto Rican kindred with X-linked retinitis pigmentosa associated with a novel RP GTPase regulator (RPGR) genotype. Methods : A total of 100 family members of a single kindred with X-linked RP were evaluated with ophthalmic examinations and blood DNA analysis. Visual fields, OCT, and full-field ERG were obtained on all affected males and carriers. Results : Of the 100 family members examined, 13 were affected males and 18 were carriers. A deletion of 2 base pair of the RPGR gene in the ORF15 region at position c.2267-2268 (Lys756del2aaAG hemi) was identified with the affected and carriers. Best eye visual acuity was correlated with age (Spearman coefficient = 0.95) with hand-motion acuity by age 35 and light perception to no light perception by age 50–60. Visual fields were minimally plottable by age 40, and ERG responses reached non-detectable levels by late teens. Carriers had no or mild visual symptoms. All carriers had visual acuity of at least 20/50 or better in one eye, and the amount of retinal degeneration was variable with ERG responses ranging from severely impaired to normal. Conclusions : Profound visual loss occurred by the second decade of life with progression to near no light perception by age 60 in this kindred of X-linked RP associated with the RPGR genotype. Female carriers maintained visual acuity with age and were identifiable by clinical and ERG examination. The information from this study is important to determine the optimal age for intervention, as new RP treatments are being developed and tested.